Efficiency of attenuating high-level acoustic impulses with double protection (earplugs and earmuffs used simultaneously) - Żera, J.; Młyński, R. (Archives of Acoustics, 2006)
The study aimed at attenuation obtained with simultaneously used earplugs and earmuffs(double protection) as opposed to hearing protective devices used singly. The measurementswere conducted for high 170-dB peak SPL, 14-μs rise time, and 0.4-ms A duration acousticimpulses. Tests were conducted for light and heavy earmuffs, combined with foam andwinged earplugs. The transmission loss method was used to assess the decrease in peak SPLand increase in A, C or D durations of waveforms of impulses recorded under the hearingprotectors. The artificial test fixture (ATF, PN EN 24869-3) was used in the measurementsmodified to accommodate for conditions of double protection with a simultaneous use of anearmuff and an earplug. Results are discussed in relation to impulse noise damage risk criteriadeveloped by CHABA, Pfander, and Smoorenburg. Double protection provides higher attenuationof peak SPL and a larger increase in the duration of impulses under hearing protectors,as compared to single protection of an earplug or an earmuff.